Drıftodontıc Approach On The Mandıbular Dentıtıon Followıng Fırst Premolar Extractıons - Hakan Kaya; Evren Öztaş; Serdar Kırlangıçoğlu; Türköz Uğur (Galenos Yayinevi, 2000)
It was reported that the mandibular anterior crowding has a tendency to treat itself during the first few months of therapy in first premolar extraction cases. The mandibular anterior teeth also have a tendency to drift distally more than mesial drift of the mandibular posterior teeth. The aim of this study is to examine spontaneous changes following first premolar extractions in the lower arch related to driftodontic approach. This study was performed on a group consisted of 10 girls who are on the growth and development period. The mean age of the group was 12.8 years at the beginning of observation period. The mean observation time was 0.5 years. Extraoral cervical pull headgear and full band-brackets applied to upper arch following first premolar extractions. No mandibular therapy was rendered. 14 linear and 2 angular parameters have been measured on 20 lateral cephalograms and 4 linear parameters also have been measured on 20 orthodontic casts taken from 10 cases, at the beginning and at the end of observation period. The statistical significance of the differences between pre and post observation measurements has been determined by the Wilcoxon test. Following statistically significant changes were determined at the end of the observation period: Spontaneous retrusion and distalization of the lower incisors, spontaneous mesial tipping and a slight extrusion of the lower molars, an increase in the intercanine distance. Otherwise, a decrease in the axial inclination of the upper incisors due to the fixed appliance therapy. The results of this investigation support the other data performed on the same subject. The canines drifted laterally and both the incisors and the canines drifted distally into the extraction sites while both of them became more upright over basal bone and the incisors less crowded. This approach allows the clinician to treat the lower arch at a later time during the therapy and the fixed appliances are less worn by the patient.